(3TQM eLeY GdHMQjfs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc,J (B801 (3g` s ((3MGLi eMeO Hf jhSa s)
(3ChdgG (B:s
(3jG ef dG jMhW ceGdg ceGdg fXGb eUa GdaUMGA, hdG jfhW HEOQGc EOQGcg CacGQ aMhd GdaVdGA s
(3BNQgG (B:s
(3bO febJ gPG GdcJGH HYhf Gddg Gdedc GdhgGH s
(3GdcJGH GdeTQhM gh eLeY GdHMQjf hedJbi GdfgQjf ai aQhY GdMfajI deXaQ GdOjf CMeO Hf Ydi Hf KYdH GdeYQha HGHf GdSGYGJi GdMfai (B- (3J (B694 (3g`s
(3GdfSNI HgG MhGTs
(3ai Ghd GdfSNI agQSJ hJedcs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs